Baseball's most wanted II : the top 10 book of more bad hops, screwball players, and other oddities - Conner, Floyd, 1951- (Potomac Books, Inc., 2003)
Baseball has so many stars and scrubs, quotables and notables - so many that one book just isn't enough to cover them all. Enter Baseball's Most WantedTM II . Starting where Baseball's Most WantedTM left off, version 2.0 introduces even more colorful characters, inept fielders and hitters, and forgotten stars as well as all the teams, fans, managers, and even announcers who are a vibrant part of baseball's past, present, and future. You'll read top-ten lists of the best and worst hitters and pitchers, the most unique memorabilia, and the most obsessed fans. Learn which president vowed to never p.